2014
DOI: 10.1371/journal.pbio.1002021
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Odors Linked to Precise Timing in the Olfactory System

Abstract: The temporal dynamics of glomeruli activity can be behaviorally discerned by mice down to 13 milliseconds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“…Here, we have shown that mammals can detect temporal features of odour stimuli at frequencies of up to 40 Hz. This surprisingly high frequency is consistent with recent findings that the olfactory bulb circuitry not only enables highly precise odour responses (Cury and Uchida, 2010;Shusterman et al, 2011) but also enables detection of optogenetically evoked inputs with a precision of 10-30 ms (Rebello et al, 2014;Smear et al, 2011). While behavioural and physiological responses to precisely timed odour stimuli have been observed in insects (Brown et al, 2005;Geffen et al, 2009;Nagel et al, 2015;Riffell et al, 2014;Szyszka et al, 2014;Vickers et al, 2001), in mammals the complex structure of the nasal cavity was generally thought to "wash-out" any temporal structure of the incoming odour plume ((Kepecs et al, 2006) see however (Gupta et al, 2015)).…”
supporting
confidence: 87%
“…Here, we have shown that mammals can detect temporal features of odour stimuli at frequencies of up to 40 Hz. This surprisingly high frequency is consistent with recent findings that the olfactory bulb circuitry not only enables highly precise odour responses (Cury and Uchida, 2010;Shusterman et al, 2011) but also enables detection of optogenetically evoked inputs with a precision of 10-30 ms (Rebello et al, 2014;Smear et al, 2011). While behavioural and physiological responses to precisely timed odour stimuli have been observed in insects (Brown et al, 2005;Geffen et al, 2009;Nagel et al, 2015;Riffell et al, 2014;Szyszka et al, 2014;Vickers et al, 2001), in mammals the complex structure of the nasal cavity was generally thought to "wash-out" any temporal structure of the incoming odour plume ((Kepecs et al, 2006) see however (Gupta et al, 2015)).…”
supporting
confidence: 87%
“…Both the spatial identity or temporal latencies of glomeruli activated in the pattern may be perceptually meaningful (6,7), but the relative importance of each is unknown. It is also unclear what forms a perceptually-meaningful combination of glomerular activation: ordered sequences aligned relative to each other (10)(11)(12), sequences aligned to sniff rhythm (6,7,13,14), or the earliest activated subset of glomeruli within a sniff rhythm (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Inhalation delivers transient pulses of odorant to the olfactory epithelium, and so determines the initial temporal structure of olfactory sensory input to the brain and drives the temporal patterning of activity at subsequent processing stages (Macrides and Chorover, 1972, Onoda and Mori, 1980, Sobel and Tank, 1993, Kepecs et al, 2006, Schaefer et al, 2006, Schaefer and Margrie, 2007, Wachowiak, 2011. Behavioral and psychophysical studies have shown that odor percepts are formed within the time of a single inhalation (150-250 ms for rodents, ~400 ms for humans) (Laing, 1986, Johnson et al, 2003, Kepecs et al, 2007, and neurophysiological studies have demonstrated that the temporal pattern of neural activity elicited by a single inhalation of odorant can robustly encode odorant identity and intensity (Uchida and Mainen, 2003, Kepecs et al, 2007, Wesson et al, 2008, Cury and Uchida, 2010, Shusterman et al, 2011, Rebello et al, 2014. Thus, understanding how inhalation-linked temporal patterns of activity are generated and shaped by neural circuits in the early olfactory pathway is fundamental to understanding olfactory information processing.…”
Section: Introductionmentioning
confidence: 99%